American political thought. - Grimes,Alan Pendleton (New York, 1964)
The role of America in world politics has made an understanding of its political thought of especial interest and significance. The underlying values of American political thought reflect in large measure the values of the Westem cultural heritage, philosophers of the West have always provided much of the intellectual grist for American theoreticians. This assumption, of the relatedness of American political to Western political philosophy, which underlay the first edition of this book, is continued in the present revision. Specifically it has seemed appropriate to include the eco nomic individualism of the former Austrian economist, Friedrich A. Hayek, now a professor in America, whose The Road to Serfdom so clearly articulates the political economic beliefs of many Americans; democratic socialism as in the as represented writings of Norman Thomas; Marxian economics, of such world importance, as represented by the writings of Paul Sweezy, and modern conservatism which has drawn no little of its inspiration from the political thought of Edmund Burke. As previously Americans drew upon the writings of f Calvin, John Locke, and John Stuart Mill, so have Americans continued to draw upon the thinkers of the West when it has served their interests to do so.
Keywords: Political Science